2014
DOI: 10.5505/tjtes.2014.09465
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of hyperbaric oxygen and ozone applications in tissue healing in generated soft tissue trauma model in rats: an experimental study

Abstract: BACKGROUND: Soft tissue trauma is a type of acute traumatic ischemia. We investigated in this study whether the edema, inflammation and ischemia caused by the trauma could be affected positively by hyperbaric oxygen (HBO) and ozone therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…A total of 29 studies using HBOT for skin wound healing were included . Fourteen studies investigated HBOT for chronic wounds, 12 studies investigated HBOT in acute wounds, one study investigated HBOT in both chronic and acute wounds and two studies were performed in experimental wound models.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 29 studies using HBOT for skin wound healing were included . Fourteen studies investigated HBOT for chronic wounds, 12 studies investigated HBOT in acute wounds, one study investigated HBOT in both chronic and acute wounds and two studies were performed in experimental wound models.…”
Section: Resultsmentioning
confidence: 99%
“…63 Yildirim et al used 63 rats with soft tissue trauma to investigate the effects of HBOT on edema, necrosis and inflammation. 53 A significant decrease in inflammation was detected in the HBO group compared to the control group. 53 T€ umerdem et al investigated the effect of HBOT on the survival of a full-thickness skin graft applied on a previously irradiated area.…”
Section: Case Seriesmentioning
confidence: 87%
See 1 more Smart Citation
“…HBOT increases the expression of diverse growth factors and activates the hypoxia-inducible factor 1 (HIF-1) that may enhance angiogenesis and fibroblast proliferation [ 14 , 15 ]. In addition, most authors have indicated that the resulting hyperoxia may cause vasoconstriction, thereby decreasing tissue oedema [ 8 , 16 ], although this oedema decrease might be cause by an inflammation reduction after HBOT [ 17 ]. HBOT treatment also induces changes in the oxidative capabilities of immune cells, which can actively participate in the process of wound healing [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It leads to reductions in antioxidant levels and shocks in the body due to the stimulating effect of hydrogen peroxide. As a result of this effect, the defense system is stimulated and thus resistance to the oxidative process is increased, including antioxidant enzyme expression [ 14 ]. Ozone therapy can increase acute cutaneous wound healing and regulate other processes, such as inflammatory responses [ 15 ].…”
Section: Introductionmentioning
confidence: 99%